Hadis Dan Politik: Kebijakan Taqlīl al-Riwāyah pada Masa Abu Bakar al-Shiddiq dan Umar Bin al-Khaṭṭāb - Amin, Ahmad; Safri, Edi; Hakim, Luqmanul (Universitas Islam Negeri Imam Bonjol Padang, 2020)
There were differences of attitudes taken by the caliphs Abu Bakr al-Siddiq and Umar bin al-Khattab in the narration of the hadith, as compared to those carried by the Prophet Muhammad. In his time, the Prophet (SAS) invited and motivated the Companions to narrate the hadith to others. But the caliphs Abu Bakr al-Siddiq and Umar bin al-Khattab carried out a different policy between the obligations of the Companions to tighten the narrations of the traditions of the Prophet SAW or called taqlid al-riwayah. The paper aims to discuss taqlid al-riwayah policy based on background, forms, and objectives. They were related to the policy and bring up the positive and negative of the application of the policy to the development of hadith in the aftermath. The results of the study found that there were political and social factors that cause policies to be taken. They oppose politics, oppose false prophets, the number of people who apostatize, and do not run Islamic law with kaffah, exchanging friends who gave false traditions. The taqlil al-riwayah policy takes various forms. They are to reduce narration, strictness (tatsabbut) in accepting competition, punishing and renewing friends who had multiply the narration of traditions. The traditions of the Prophet Muhammad were from mistakes and falsification. Besides, this policy also opposes the development of traditions, both regarding the positive, preserved, authenticity and quality of the traditions of the Prophet SAW and also does not violate false traditions (maudhu ') among Muslims. It is also free of negative impacts. According to part of the distribution and the list of traditions, the Prophet (PBUH), the lively discussion of hadith meanings and the delay in the process of codifying the traditions of the Prophet PBUH.